A Single Dose of an MVA Vaccine Expressing a Prefusion-Stabilized SARS-CoV-2 Spike Protein Neutralizes Variants of Concern and Protects Mice From a Lethal SARS-CoV-2 Infection - Pérez, Patricia; Lázaro-Frías, Adrián; Zamora, Carmen; Sánchez-Cordón, Pedro J.; Astorgano, David; Luczkowiak, Joanna; Delgado, Rafael; Casasnovas, José M.; Esteban, Mariano; García-Arriaza, Juan (Frontiers in Immunology, 2022)
We generated an optimized COVID-19 vaccine candidate based on the modified vaccinia virus Ankara (MVA) vector expressing a full-length prefusion-stabilized SARS-CoV-2 spike (S) protein, termed MVA-CoV2-S(3P). The S(3P) protein was expressed at higher levels (2-fold) than the non-stabilized S in cells infected with the corresponding recombinant MVA viruses. One single dose of MVA-CoV2-S(3P) induced higher IgG and neutralizing antibody titers against parental SARS-CoV-2 and variants of concern than MVA-CoV2-S in wild-type C57BL/6 and in transgenic K18-hACE2 mice. In immunized C57BL/6 mice, two doses of MVA-CoV2-S or MVA-CoV2-S(3P) induced similar levels of SARS-CoV-2-specific B- and T-cell immune responses. Remarkably, a single administration of MVA-CoV2-S(3P) protected all K18-hACE2 mice from morbidity and mortality caused by SARS-CoV-2 infection, reducing SARS-CoV-2 viral loads, histopathological lesions, and levels of pro-inflammatory cytokines in the lungs. These results demonstrated that expression of a novel full-length prefusion-stabilized SARS-CoV-2 S protein by the MVA poxvirus vector enhanced immunogenicity and efficacy against SARS-CoV-2 in animal models, further supporting MVA-CoV2-S(3P) as an optimized vaccine candidate for clinical trials.